Aristophanes and Euripides - Gil, Luis (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2013)
Aristophanes’ ambivalent mix of admiration and hatred with respect to Euripides can be inferred from examination (I) of the nominatim references, the passages in which he is partially or totally quoted or imitated (II), and his role in plays where he features as a character (III). Aristophanes considers Euripides as a poet σοφός, γενναῖος, γόνιμος, στρεψίμαλλος τὴν τέχνην and πανοῦργος. He quotes and imitates him (II) not only to deride his pedantically affected and sentencious style (κομψευριπικῶς), but also to condemn his thought when he deems it harmful or morally dangerous. As a character Euripides plays (III) the positive role of helping the comic hero in Ach. and Thesm. In Ran. Dionysus presents him as a tragic poet on an equal footing with Aeschylus and only political reasons move him to take Aeschylus along to Athens: his favourable attitude towards Alcibiades. Politics also explain the criticism in Ran. with regard to certain aspects in Euripidean drama such as the excessive pathos and the ‘democratisation’ of characters, which for Aristophanes entail a downgrading of tragedy.